V.A.T nown; Gay Lessons; Dagyaw [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1994)
Summary: Documents the value added tax issue; the Gay literature course offered by U.P. Diliman English Department; the Dagyaw theater and dance company made up of high school students in Iloilo City.
Contents: V.A.T nown (17 min.) -- Gay Lessons (20 min.) -- Dagyaw (13 min.).
VHS.
Credits: Reporter, Luchi Cruz Valdes.
Keywords: Dagyaw Dance Group (Iloilo City).; Value added tax -- Philippines. -- Law and legislation; Homosexuality and literature -- Philippines